Pediatric Urinary Stones Compositions and its Relations with Age and Gender in Al-muthanna Governorate, Iraq - Al-Hamdani, Hussein Ali (International Journal of Psychosocial Rehabilitation, 2020)
Background: Pediatric urolithiasis results in significant morbidity in later life. Incidence as well as site and chemical composition of calculi varies according to the changes in socio-economic and dietary habits leading to a marked variation in the spectrum of urinary stone composition. To evaluate the spectrum of urinary stone composition in pediatric population from al muthanna governorate, Iraq and its relations with age group and gender. Methods: This was a prospective observational study conducted between October 2018 and February 2020 which included pediatric patients with urolithiasis. Demographic and epidemiological characteristics including age, sex, geography, socio-economic status, dietary habits were recorded. The location and sizes of stones were documented. The data was collected, analyzed by Fourier transform infrared spectroscopy (FTIR) and presented using summary statistics. Results: A total of 149 patients with urolithiasis were enrolled, of which 65.1% male and 34.9% female with male to female ratio 1.87:1, Calcium oxalate 30.2%,uric acid 16.1%,mixed 9.4%,cysteine 34.2%, and phosphate stone 10.1% Conclusions: the prevalence of calcium oxalate and uric acid stones were more common in school aged children while cysteine and mixed stones were more common in preschool age children with high incidence of phosphate stone in female patients.